A Comparison of the PlusoptiX S04 and A09 Photoscreeners. (June 2013) - Singman, Eric; Matta, Noelle; Tian, Jing; Brubaker, Abby; Silbert, David
Abstract Purpose: We compare the plusoptiX S04 and A09 photoscreeners on a single cohort of children. Methods: One hundred and thirteen children were evaluated on both the plusoptiX S04 and A09 photoscreener. A lay screener performed all of the testing prior to a pediatric ophthalmology examination. The order was alternated so that the S04 was performed first on one patient then second on the next to minimize fatigue bias. Results: Utilizing our modified criteria previously published, the plusoptiX S04 was found to have a sensitivity of 85%, specificity of 94%, false positive rate of 15%, and false negative rate of 6% in detecting American Association for Pediatric Ophthalmology and Strabismus–defined amblyopia factors. The plusoptiX A09 was found to have a sensitivity of 92%, specificity of 88%, false positive rate of 11%, and false negative rate of 8%. Conclusion: The plusoptiX S04 and A09 photoscreeners perform similarly when used by a lay screener to evaluate the same population of children.